Vocal Age Disguise: The Role of Fundamental Frequency and Speech Rate and Its Perceived Effects - Skoog Waller, Sara; Eriksson, Mårten (Frontiers in Psychology, 2016)
The relationship between vocal characteristics and perceived age is of interest in various contexts, as is the possibility to affect age perception through vocal manipulation. A few examples of such situations are when age is staged by actors, when ear witnesses make age assessments based on vocal cues only or when offenders disguise their voice to appear younger or older. This paper investigates how speakers spontaneously manipulate two age related vocal characteristics (f0 and speech rate) in attempt to sound younger versus older than their true age, and if the manipulation corresponds to actual age related changes in f0 and speech rate (Study 1). Further aims of the paper is to determine how successful vocal age disguise is by asking listeners to estimate the age of generated speech samples (Study 2) and to examine whether or not listeners use f0 and speech rate as cues to perceived age. In Study 1, participants from three age groups (20-25, 40-45 and 60-65 years) agreed to read a short text under three voice conditions. There were 12 speakers in each age group (six women and six men). They used their natural voice in one condition, attempted to sound 20 years younger in another and 20 years older in a third condition. In Study 2, 60 participants (listeners) listened to speech samples from the three voice conditions in Study 1 and estimated the speakers’ age. Each listener was exposed to all three voice conditions. The results from Study 1 indicated that the speakers increased fundamental frequency (f0) and speech rate when attempting to sound younger and decreased f0 and speech rate when attempting to sound older. Study 2 showed that the voice manipulations had an effect in the sought-after direction, although the achieved mean effect was only 3 years, which is far less than the intended effect of 20 years. Moreover, listeners used speech rate, but not f0, as a cue to speaker age. It was concluded that age disguise by voice can be achieved by naïve speakers even though the perceived effect was smaller than intended.